CCIE voice exam quick reference sheets - Lewis, Mark (Shortcut, 2007)
CCIE Voice Exam Quick Reference Sheets (Digital Short Cut) Mark Lewis ISBN-10: 1-58705-333-0 ISBN-13: 978-1-58705-333-7 ¿ As a final exam preparation tool, the CCIE Voice Exam Quick Reference Sheets provides a concise review of all objectives on the new CCIE Voice written exam (350-030). This digital Short Cut provides you with detailed, graphical-based information, highlighting only the key topics in cram-style format. ¿ With this document as your guide, you will review topics on Cisco CallManager and Unity; QoS; telephony protocols; IOS IP telephony; IP IVR; IPCC; voice security, operations, and management; and infrastructure and application protocols. These fact-filled Quick Reference Sheets allow you to get all-important information at a glance, helping you focus your study on areas of weakness and to enhance memory retention of essential exam concepts. ¿ Table of Contents Introduction 1.¿¿¿¿¿ Cisco CallManager 2.¿¿¿¿¿ Understanding Quality of Service (QoS) 3.¿¿¿¿¿ Telephony Protocols 4.¿¿¿¿¿ Cisco Unity 5.¿¿¿¿¿ IOS IP Telephony Skills 6.¿¿¿¿¿ IP Interactive Voice Response (IP IVR)/IP Contact Center (IPCC) Express 7.¿¿¿¿¿ Security 8.¿¿¿¿¿ Infrastructure Protocols 9.¿¿¿¿¿ Application Protocols 10.¿ Operations and Network Management ¿ ¿ About the author: Mark Lewis, CCIE No. 6280, is technical director of MJL Network Solutions, a provider of internetworking solutions that focuses on helping enterprise and service provider customers implement leading-edge technologies, including VoIP/IP telephony solutions. Mark specializes in next-generation/advanced network technologies and has extensive experience designing, deploying, and migrating large-scale IP/MPLS networks and VoIP/IP telephony solutions. He is an active participant in the IETF, a member of the IEEE, and a Certified Cisco Systems Instructor (CCSI). ¿ Mark is the author of the Cisco Press titles Comparing, Designing, and Deploying VPNs (ISBN 1-58705-179-6) and Troubleshooting Virtual Private Networks (ISBN 1-58705-104-4). ¿